2001
DOI: 10.1152/jappl.2001.91.5.2088
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in cardiovagal baroreflex gain in humans

Abstract: We tested the hypothesis that women would demonstrate lower cardiovagal baroreflex gain compared with men. If so, we further hypothesized that the lower cardiovagal baroreflex gain in women would be associated with their lower aerobic fitness and higher body fat percentage compared with men. To accomplish this, we measured cardiovagal baroreflex gain (modified Oxford technique) in sedentary, nonobese (body mass index < 25 kg/m2) men (age = 26.0 +/- 2.1 yr, n = 11) and women (age = 26.9 +/- 1.6 yr, n = 14). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 32 publications
10
59
2
1
Order By: Relevance
“…10 Indeed, the gender-related difference in BRB in the present study was almost as great as the difference recently found between healthy adults and patients with long-standing essential hypertension. 10,16 Thus, consistent with previous reports of gender-related differences in other ANS-cardiovascular functions, [1][2][3][4]8,[23][24][25] the present findings indicate that subject gender is a major source of interindividual variability in tonic ANS support of BP and BRB of BP in healthy adult humans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10 Indeed, the gender-related difference in BRB in the present study was almost as great as the difference recently found between healthy adults and patients with long-standing essential hypertension. 10,16 Thus, consistent with previous reports of gender-related differences in other ANS-cardiovascular functions, [1][2][3][4]8,[23][24][25] the present findings indicate that subject gender is a major source of interindividual variability in tonic ANS support of BP and BRB of BP in healthy adult humans.…”
Section: Discussionsupporting
confidence: 92%
“…This effective blocking dose was maintained throughout the experimental session. Complete cardiovascular-autonomic blockade was documented by an absence of change in heart rate (Ͻ5 bpm) in response to the acute increase in BP (Ն15 mm Hg) produced by bolus administration of phenylephrine (25,50, and/or 100 g). BRB was measured in a subgroup of 14 women and 14 men (aged 26Ϯ1 and 27Ϯ1 years, respectively) as the potentiation of the SBP response to a standard 25-g bolus dose of phenylephrine during GB compared with before GB.…”
Section: Autonomic-cardiovascular Functionmentioning
confidence: 99%
“…27 In our study, it was not possible to analyze gender effects. Thus, our results should be restricted to measuring S-BRS decrease between 18 and 50 years in a male population.…”
Section: Limitationsmentioning
confidence: 87%
“…Women had a greater increase of heart rate during steady-state orthostatic stress. There have been many animal studies that indicate that estrogen supplementation enhances baroreceptor function in ovariectomized female animals (12,22,41); however, it has been shown that women have less sensitive baroreceptors than men (3,63). Therefore, the greater increase in heart rate is not likely due to differences in cardiovagal baroreflex gain, which would result in a smaller increase of heart rate.…”
Section: Discussionmentioning
confidence: 99%